Managing Operational Risks in Water Supply Sector - Kandiana Wati; Mukhamad Najib; Setiadi Djohar (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2019)
Abstract. Water and sanitation sector is characterized with having many risks. The ability to manage risks is one of the success factors in providing clean water services to the community. The objective of this paper is to identify the operational risks in the water supply provision, to analyze the significant risks, and to formulate actions to manage the significant risks. The operational risks are analyzed using probability impact matrix. The research shows that the significant operational risks mostly occur during raw water extraction process, which are risks related to the quality and quantity of raw water, as well as reliability of the supporting facilities (intake and transmission pipe). Other significant risks are production failure, intermittent supply, low water pressure, and contractor availability for meter installation. Because significant operational risks are caused by process and external factor, the proposed risk management includes the development of procedures and guidelines, as well as the implementation of effective contractor management. Risk management also includes the establishment of effective communication and coordination with relevant stakeholders. Keywords: Operational risk, probability impact matrix, risk management, water company, water supply provisionAbstrak. Sektor air dan sanitasi memiliki banyak risiko. Kemampuan untuk mengelola risiko yang muncul menjadi salah satu faktor keberhasilan penyediaan air bersih bagi masyarakat. Penelitian ini bertujuan untuk mengidentifikasi risiko operasional dalam penyediaan air bersih, menganalisa risiko yang signifikan, serta memformulasikan langkah-langkah penanganan risiko yang signifikan. Analisa risiko operasional dilakukan menggunakan matriks probability impact. Hasil penelitian menunjukkan bahwa risiko operasional signifikan paling banyak terjadi pada proses pengambilan air baku, yaitu risiko yang terkait kualitas dan kuantitas air baku, serta kehandalan fasilitas pendukung (bangunan sadap dan pipa transmisi). Risiko signifikan lainnya yaitu kegagalan produksi, gangguan suplai, tekanan air kecil, dan ketersediaan kontraktor pemasangan meter. Karena risiko operasional yang signifikan disebabkan oleh faktor proses dan eksternal, pengelolaan risiko yang diusulkan meliputi penyusunan prosedur dan pedoman kerja, serta penerapan pengelolaan kontraktor yang efektif. Pengelolaan risiko juga meliputi pengembangan komunikasi dan koordinasi yang efektif dengan pemangku kepentingan yang terkait.Katakunci: Matriks probability impact, pengelolaan risiko, penyediaan air bersih, perusahaan air bersih, risiko operasional.